Listeria monocytogenes cross-contamination during apple waxing and subsequent survival under different storage conditions. (April 2023) - Shen, Xiaoye; Su, Yuan; Hua, Zi; Zhu, Hongmei; Ünlü, Gülhan; Ross, Carolyn; Mendoza, Manoella; Hanrahan, Ines; Tang, Juming; Zhu, Mei-Jun
Abstract: This study evaluated Listeria monocytogenes cross-contamination between inoculated fruits, waxing brush, and uninoculated fruits during apple wax coating and investigated the fate of L. monocytogenes on wax-coated apples introduced via different wax coating schemes. There were 1.8–1.9 log10  CFU/apple reductions of L. monocytogenes on PrimaFresh 360, PrimaFresh 606, or Shield-Brite AP-450 coated apples introduced before wax coating after 6 weeks of ambient storage (22 °C and ambient relative humidity). L. monocytogenes showed a similar trend ( P  > 0.05) on waxed apples under cold storage (1 °C and ∼ 90% relative humidity); there were 1.8–2.0 log10  CFU/apple reductions of L. monocytogenes during the 12 weeks of cold storage regardless of wax coating type. For cross-contamination study, a waxing brush was used to wax one inoculated apple (6.2 log10  CFU/apple); then, this brush was used to wax five uninoculated apples in a sequence. There were 3.7, 3.5, 3.3, 2.9, and 2.7 log10  CFU/apple and 3.6 log10  CFU/brush of L. monocytogenes transferred from the inoculated apple to uninoculated apple 1 to apple 5, and the waxing brush, respectively. The die-off rate of L. monocytogenes on wax-coated apples contaminated during wax coating was not significantly different from that contaminated on apples before wax coating, and 1.8–1.9 log10  CFU/apple reductions were observed during the 12 weeks of cold storage. The application of wax coatings, regardless of wax coating type, did not impact the survival of endogenous yeasts and molds on apples during ambient or cold storage. L. monocytogenes transferred onto waxing brushes during wax coating remained relatively stable during the 2-week ambient holding. Fungicide application during wax coating reduced ( P  < 0.05) yeast and mold counts but had a minor impact ( P  > 0.05) on the survival of L. monocytogenes on apples after 12 weeks of cold storage. Collectively, this study indicated that a high cross-contamination risk of L. monocytogenes during apple waxing, and L. monocytogenes on wax-coated apples introduced via different scenarios is stable during subsequent cold storage, highlighting the need for potential intervention strategies to control L. monocytogenes on wax-coated apples. Highlights: There is a high cross-contamination risk of L. monocytogenes ( Lm ) during apple waxing. 3.7 log of Lm transferred from inoculated (6.2 log) to clean apples during waxing. Culturable Lm reduced by ∼2.0 log on waxed apple during 12-week cold storage. Fates of Lm on apples introduced before or during waxing was not different ( P  > 0.05). Fungicides included in wax coating reduced yeasts/molds but not L. monocytogenes .